The Effect Of Price Earning Ration And Risk (Beta) On Company Stock Returns In Mining Industry Companies Listed On The Indonesia Stock Exchange - Suriyanti, Suriyanti; Cahya Firman Agung P; Harmelia Ridwan Saleh; A. Dallatika; Yuli Ashaniais Ramadani; Lisa Rizky Fauziah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study aims to determine the effect between Price Earning Ratio and Risk (Beta) on Stock Returns. The research method used is quantitative research. The object of this research is Mining Industry Companies listed on the Indonesia Stock Exchange in 2021-2023. The sample selection used purposive sampling method with a total sample of 10 Mining Industry Companies. The data in this study uses secondary data obtained from the Indonesia Stock Exchange website and the website of each company. The analysis technique used is multiple linear regression analysis using the Statistical Package for Social Science (SPSS) for Windows 26 software application. The results of the hypothesis test show that the price earning ratio variable has a positive and significant effect on stock returns. This means that the higher the price earning ratio, the effect on increasing stock returns and the results of hypothesis testing show that the Risk (Beta) variable has a negative and significant effect on stock returns. This means that the higher the Risk (Beta), the effect on the decrease in stock returns.